How the endosymbiont got its cell - Poole, Anthony (New Zealand Science Review, 2009)
Despite fundamental advances in cellular, molecular and genome biology, there is still surprisingly little consensus concerning the evolutionary origins of the eukaryote cell. While it is clear that the mitochondrion (responsible for generating much of the energy requirements of the eukaryote cell) has evolved from an endosymbiont cell of bacterial origin, the recent literature has borne witness to a tidal wave of speculative theories regarding the nature of the cell in which this bacterium took up residence. David Penny and I recently argued that much of this confusion can be avoided if models are grounded in known biological processes, and if speculation is tempered by formulating testable hypotheses. The most fanciful hypotheses are an inevitable casualty of a pragmatic approach, but what remains is a productive framework wherein biologically plausible alternatives can be evaluated without the need to invoke ad hoc events or processes, such as biological ‘big bangs’ or hitherto unobserved cell biological phenomena.